Forgiveness between remembrance and forgetting: Overcoming the power of past evil - Zachhuber, J (Mohr Siebeck, 2015)
In this chapter, I try to explain remembrance and forgetting with regard to human temporality. We need both, I argue, in order to maintain (or restore) our full integrity as existing in past, present, and future. forgiveness, I then suggest, can be inscribed into the same structure. It needs both remembrance and forgetting in order to become possible. I close my argument with some reflections on the possibility of divine forgiveness and divine forgetting.